Clarifying the paradigm for the ethics of donation and transplantation: Was 'dead' really so clear before organ donation? - Shemie, Sam D (BioMed Central|1, 2007)
Recent commentaries by Verheijde et al, Evans and Potts suggesting that donation after cardiac death practices routinely violate the dead donor rule are based on flawed presumptions. Cell biology, cardiopulmonary resuscitation, critical care life support technologies, donation and transplantation continue to inform concepts of life and death. The impact of oxygen deprivation to cells, organs and the brain is discussed in relation to death as a biological transition. In the face of advancing organ support and replacement technologies, the reversibility of cardiac arrest is now purely related to the context in which it occurs, in association to the availability and application of support systems to maintain oxygenated circulation. The 'complete and irreversible' lexicon commonly used in death discussions and legal statutes are ambiguous, indefinable and should be replaced by accurate terms. Criticism of controlled DCD on the basis of violating the dead donor rule, where autoresuscitation has not been described beyond 2 minutes, in which life support is withdrawn and CPR is not provided, is not valid. However, any post mortem intervention that re-establishes brain blood flow should be prohibited. In comparison to traditional practice, organ donation has forced the clarification of the diagnostic criteria for death and improved the rigour of the determinations.